Oral health-related dietary knowledge and habits among the students of Isfahan University and Isfahan University of Medical Sciences in spring 2012 - Zahra Saied-Moallemi; Zahra Enshaei (Isfahan University of Medical Sciences, 2013)
AbstractIntroduction: Diet is one of the factors affecting oral health. Recent nutrition transition in Iran has led to increased consumption of high-calorie sources (bread, sugar and fats), especially in younger people in different levels of education. This study aimed to assess oral health-related dietary knowledge and habits among the students of Isfahan University and Isfahan University of Medical Sciences.Materials and Methods: This cross-sectional study investigated oral health-related dietary knowledge and habits among 320 students of Isfahan University (in four schools) and 215 students of Isfahan University of Medical Sciences (in five schools) with at least four semesters of study at the university. The study was carried out in the second half of the academic year 2011-2012. After assessing the validity and reliability (ICC > 0.7) of the self-administered questionnaire, data were collected through distribution in classroom. Descriptive analyses and chi-squared test were applied (α = 0.05).Results: The results showed that the mean scores for knowledge of students about cariogenicity of different foods and the role of diet in oral health was 31.2 ± 7 (out of 48) and 4.7 ± 1.5 (out of 8), respectively. Students of Isfahan University of Medical Sciences were significantly more knoeledgeable than the students of Isfahan University (p value < 0.001). The mean score of their oral health-related dietary habits was 15.44 ± 4.3 (out of 32), with no significant difference between the students of the two universities (p value > 0.05).Conclusion: Oral health-related dietary knowledge of the students of Isfahan University and Isfahan University of Medical Sciences was generally moderate and their oral health-related dietary habits were poor. Appropriate strategies should be planned to improve oral health-related dietary knowledge and habits among university students. Key words: Cariogenic diet, Dietary habit, Knowledge, Oral health